“An Essay on the True Art of Varying: C. P. E. Bach’s Sonatas with Varied Reprises” - Beghin, Tom (Mechelen Evil Penguin Classic, 2024)
Elucidates the historical, socio-cultural, and rhetorical context for C. P. E. Bach’s publication of Sonatas with Varied Reprises (1760), as well as the performance decisions made for a recording of Bach’s original set (CD 1), along with additional variants by Bach himself (CD 2).
Abstract:Elucidates the historical, socio-cultural, and rhetorical context for C. P. E. Bach’s publication of Sonatas with Varied Reprises (1760), as well as the performance decisions made for a recording of Bach’s original set (CD 1), along with additional variants by Bach himself (CD 2).
FRIS
0
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850